Timing of venous thromboembolism chemoprophylaxis using objective hemoglobin criteria in blunt solid organ injury. Issue 5 (May 2023) - Marturano, Matthew N.; Khan, Ahsan R.; DeBlieux, Paige; Wang, Huaping; Ross, Samuel W.; Cunningham, Kyle W.; Sing, Ronald F.; Thomas, Bradley W.
Highlights: Optimal timing of VTE chemoprophylaxis in blunt solid-organ injuries is controversial and varies by provider and institution. By establishing an objective guideline, chemoprophylaxis can be started early while being agnostic of concomitant injuries. Our guideline was that enoxaparin was initiated when patients had <1g/dl Hemoglobin decline over a 24 h period. Patients initiated <48 h from admission suffered fewer VTE events, had no difference in blood transfusions or nonoperative failure. Abstract: Background: The purpose of this study was to evaluate the safety and efficacy of early venous thromboembolism (VTE) chemoprophylaxis following blunt solid organ injury. Methods: A retrospective review of patients was performed for patients with blunt solid organ injury between 2009–2019. Enoxaparin was initiated when patients had <1g/dl Hemoglobin decline over a 24 h period. These patients were then categorized by initiation: ≤48 h and >48 h. Results: There were 653 patients: 328 (50.2%) <48 h and 325 (49.8%) ≥48 h. Twenty-nine (4.4%) developed VTE. Patients in ≥48 h group suffered more frequent VTE events (6.5% vs 2.4%, p = 0.021). Non-operative failure occurred in 6 patients (1.9%) in ≥48 h group, and 5 patients (1.5%) < 48 h group. Blood transfusion following chemophrophylaxis initiation was required in 69 (21.3%) in ≥48 h group, and 46 (14.0%) in < 48 h group, occurring similarly between groups (p=0.021). Conclusion: Stable hemoglobin in the first 24 h is an efficacious, objective measure that allows early initiation of VTE chemoprophylaxis in solid organ injury. This practice is associated with earlier initiation of and fewer VTE events.